Diachronic and Achronic Nature of Old Armenian Diphthongoids Deriving from IE Diphthongal System - Petrosyan, Vardan (Bulletin of Yerevan University B: Philology, 2023)
The attempts of diachronic examination of the diphthongal system of Old Armenian in Armenian Studies were of episodic nature. As a matter of fact, it was the diphthongal units, which were in some genealogical relation with the IE diphthongal system, that underwent examination.The diachronic approach applied in the current research reveals the ancestral relation between the Old Armenian diphthongoids աւ (aṷ), եւ (eṷ), իւ (iṷ), այ (ai̭), ոյ (oi̭) and the diphthongal and non-diphthongal prototypes of the IE base-language. Afterwards, the achronic approach, i.e. through typological parallels between the borrowings from IE and non-IE languages, as well as through the application of the statistical method, helps provide grounds to explain why a certain IE diphthong should be regarded as the main prototype of a given Armenian diphthongoid, regardless of the fact thatsometimes a single Armenian diphthongoid corresponds to more than one IE diphthongal prototype (cf. Arm. աւ (aṷ) < IE. *eu, *āu, ոյ (oi̭) < IE. *eu, *ou),there are also non-diphthongal units among IE prototypes (cf. Arm. եւ (eṷ) < *ēṷ. աղբեւր < *bhrēṷr̥,- իւ (iṷ) < IE. *ii̭. ձիւն < *ghii̭ōm):
Keywords: H. Hubshman; H. Pedersen dipthongoid prototype; non-dipthongal prototype; diachronic aspect; achronic aspect